The Practice of the Bakelewang Tradition among the Samawa People in Developing a Sense of Responsibility - Cahyani, Rani; Yuliatin, Yuliatin; Alqadri, Bagdawansyah; Zubair, Muh. (Jurnal Penelitian Medan Agama, 2025)
This study aims to analyze the implementation of the bakelewang tradition in the Samawa tribe community in forming a character of responsibility. The research method uses a qualitative approach with an ethnographic type. Data collection techniques used are interviews, observation and documentation. Data analysis techniques use data reduction, data presentation and conclusions. The results of this study indicate that the stages of implementing the bakelewang tradition in the Samawa tribe community in forming a character of responsibility, namely: 1) preparation stage, namely family deliberation (family deliberation), Committee Meeting, inviting (inviting) and forms of responsibility, namely leading the Deliberation/meeting, selecting the core committee, committee members and dividing the tasks of each member, recording and submitting the amount of assistance and recording the parties invited and delivering the contents of the invitation. 2) the implementation stage, namely antat panulung (delivering aid) and bakelewang and the forms of responsibility are, namely storing aid, supervising all activities, completing all work both in the kitchen and outside the kitchen, and 3) the closing stage, namely mangan barema (eating together) and the forms of responsibility are, namely preparing the menu, entertaining, and cleaning the place and utensils used for eating.